Hospitalité épistémique et pédagogie universitaire : l’égalité et ses problèmes - Christophe Point (Éducation et Socialisation)
Since the work of Levinas and Derrida, the hospitality is no longer a new value. However, it remains curiously less involved in questions of ethics and university pedagogy. Nevertheless, we would like to defend that hospitality, thought by the pragmatist philosophy, can be a central notion to solve the following question : what equality do we want for the university ? The aim of our argument is double. First, we will show how the liberalism currently at work in universities is dangerously setting equality and diversity against each other, and how this is at the very heart of our daily teaching practices. Then, against this liberal orientation, we will propose ways to develop a different university ethic based on the notion of hospitality to oneself, to others and to knowledge. The aim is to promote an equality in the university that grows and regenerates itself from differences rather than from their denial or negation.